Remember Vukovar: Memory, Sense of Place, and the National Tradition in Croatia - Kardov, Kruno (2004)
The war has brought significant changes in the Croatian society including the very foundation of the Croatian state. In this paper author discusses deeper processes related to this change by analysing the construction of the central place of the Croatian national identity. The city of Vukovar, as is argued, became the symbol of the birth of Croatian state and of the sacrifice of the Croatian people. By creating “ place of memory” within the national space, that is by territorialization and localization of memory, a stable order was built in which a precise social and geographical location is assigned to war. This new order which superseded the state of emergency at the national level is still under constant threat of dissolution at the local level for inside the place of Vukovar the national narratives do not have the same stabilizing and ordering power. The combination of pre-war ethnic spatial population arrangement and post-war identities gave rise to very specific problems related to the sense of place and to the war memories among the citizens of Vukovar. In this context, newly created places act as other-oriented places and memories act as counter-memories.